Experience of wrong-site tooth extraction among Nigerian dentists - Wasiu L. Adeyemo; Olabisi H. Oderinu; Akanbi C.O. Olojede; Azeez A. Fashina; Adeshina O.S. Ayodele (Elsevier, 2011)
Objective: To report the experience of wrong-site tooth extraction among Nigerian dentists. Study design: A self-administered questionnaire was distributed among a cross-section of Nigerian dentists. Information requested included personal experience on wrong-site tooth/teeth extraction and its after-effect, possible reasons for wrong-site tooth extraction and documentation of the event in patients' case. Respondents were also asked if they were aware of any colleagues who had previously experienced wrong-site tooth extraction and possible legal implication of the event, and if they aware of the universal protocol for preventing wrong site, wrong procedure, and wrong person surgery. Results: Twenty-two (13%) of the respondents reported having extracted a wrong tooth. The event occurred within 5 years after graduation in most cases. Most respondents (53.6%) informed the patient immediately after the event. Only 68% of the respondents documented the event in patient's case record. Most common reasons for wrong-site tooth extraction were heavy workload, presence of multiple condemned teeth and miscommunication between dentists. Fifty-five percent of respondents were aware of a colleague who had extracted a wrong tooth. The most probable legal implication of wrong-site tooth extraction according to the respondents was litigation by the patient. Only 25% of dentists were aware of a universal protocol for preventing wrong-site surgery. Conclusions: Wrong tooth/teeth extraction is not an uncommon event in the studied environment. The need to be familiar with universal protocol on wrong-site surgery and its legal implications are highlighted. Keywords: Wrong-site, Tooth, Extraction, Dentists